2018
DOI: 10.1002/jsfa.9198
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of inactivation mechanisms of Bacillus amyloliquefaciens spores in non‐thermal plasma of ambient air

Abstract: Progressive erosion of spore surface by NTP-AA with ensuing or concomitant biochemical damage, which includes the alteration of structural proteins, internal lipids and the loss of dipicolinic acid content from the spore core, represent the main mechanisms of inactivation, and there is evidence that reactive NTP-AA species could penetrate the cortex and reach the core of spores to cause damage. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
(112 reference statements)
2
11
0
Order By: Relevance
“…Active substances in NTP (such as reactive oxygen species, free groups, etc.) react with proteins and nucleic acids in microorganisms, disrupting the normal function of the microorganisms [ 106 , 107 ].…”
Section: Analysis Of Fruits and Vegetables Cleaning Processmentioning
confidence: 99%
“…Active substances in NTP (such as reactive oxygen species, free groups, etc.) react with proteins and nucleic acids in microorganisms, disrupting the normal function of the microorganisms [ 106 , 107 ].…”
Section: Analysis Of Fruits and Vegetables Cleaning Processmentioning
confidence: 99%
“…It has been presumed that the physical and chemical factors could act independently or in synergy in plasma treatments. Multiple mechanisms participating in plasma-cell interactions have been described: (a) pore formation and cell erosion through etching by atomic and molecular radicals, (b) photo-desorption and subsequent chemical bond breakage, (c) direct DNA destruction triggered by UV irradiation and reactive species, and (d) formation, diffusion, and accumulation of oxygenated species that induce oxidative damage to lipids, proteins (cysteine and amino acids with aromatic rings), polysaccharides, and DNA (Takai et al 2012;Lackmann et al 2013;Graves 2014;Arjunan et al 2015;Edengeiser et al 2015;Van Der Paal et al 2016;Brun et al 2018;Handorf et al 2018;Huang et al 2018;Ji et al 2018;Sakudo et al 2018;Šimončicová et al 2018).…”
Section: Mode Of Plasma Actionmentioning
confidence: 99%
“…CAPP applications in microbial decontamination has become especially important when traditional disinfection techniques fail or the inactivation of resistant bacterial strains such as methicillin-resistant S. aureus (Liao et al 2018a) or sporeforming Bacillus amyloliquefaciens (Huang et al 2018) has to be eradicated. The differences related to cell structure, size, cell density, metabolic activity, and ability to deal with reactive molecules in microorganisms still remain not well understood.…”
Section: Bacterial Decontaminationmentioning
confidence: 99%
“…NTP also affects biomolecules by inducing changes in their chemical properties or structures, leading, for example, to reduced enzyme activity and other desirable functional or molecular alterations. [49][50][51][52] In an exemplified study, cold plasma was noted to effectively reduce the number of pathogenic bacteria such as E. coli and Salmonella on apple; the longer the treatment time, the greater the decrease in the number of pathogenic bacteria. 53 In another study, where chub mackerel was treated with atmospheric cold plasma, it was found that the chemical, microbiological, and sensory properties of the fish remained the best when treatment was conducted at 60 kV for 60 s. Atmospheric cold plasma treatment not only prolonged the shelf life of the fish, but also inhibited lipid oxidation without destroying the fish tissue structure.…”
Section: Combined Ultrasonic Cleaning With Ozonementioning
confidence: 99%
“…NTP can effectively inactivate bacteria, fungi, viruses, and other microorganisms on food surfaces. NTP also affects biomolecules by inducing changes in their chemical properties or structures, leading, for example, to reduced enzyme activity and other desirable functional or molecular alterations 49–52 …”
Section: Ultrasonic and Ultrasound‐assisted Cleaning Technologiesmentioning
confidence: 99%